(untitled) (Indonesian Art and Justice Review, 2024)
The Indonesian art market has seen significant growth in recent years, yet disparities in economic access and representation remain significant issues for many artists, particularly those from marginalized communities. This paper investigates the economic inequalities within the Indonesian art market, exploring the ways in which market forces, institutional structures, and cultural hierarchies create barriers for emerging artists, particularly those from rural areas or lower socio-economic backgrounds. It critically examines the roles of galleries, auction houses, and international collectors in shaping the visibility and financial success of Indonesian artists. The paper also considers alternative models of art distribution and sales, such as community-based art markets and grassroots initiatives, that aim to address these economic disparities and promote greater fairness in the art world.